ANALISIS PEMBELAJARAN PKN DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KESADARAN SISWA BERBANGSA DAN BERNEGARA KELAS V SDN 101944 DELI MUDA - Widya Rahmawani; Sujarwo; Sutikno; Rahmat Kartolo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Problem Based Learning (PBL) model in Civic Education and its effect on the national awareness of fifth-grade students at SDN 101944 Deli Muda. The research employed a qualitative method with observation, interview, and documentation techniques. The results showed that the teacher implemented PBL well (average score 2.6), most students scored above 80, and students’ national awareness was in the good category. Thus, PBL is effective in improving PKn learning outcomes and fostering students’ national awareness.